Tourist destinations structure and synthesis - Pearce, Douglas G. 1949- (CABI, 2021)
Destination research today has become increasingly fragmented as studies become more specialized. This book provides a systematic examination and combines spatial and organizational structure across destinations from the national to the local scale to produce a comprehensive understanding of destinations and a complete integrative framework of them"--